2006
DOI: 10.1161/01.str.0000208205.26253.96
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Neuroprotectant Granulocyte-Colony Stimulating Factor

Abstract: Background and Purpose-Granulocyte-colony stimulating factor (G-CSF) is a growth factor that orchestrates the proliferation, differentiation, and survival of hematopoietic progenitor cells. It has been used for many years in clinical practice to accelerate the recovery of patients from neutropenia after cytotoxic therapy. However, there is a growing body of evidence from experimental studies suggesting that G-CSF also has important nonhematopoietic functions in the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
82
4
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 64 publications
0
82
4
4
Order By: Relevance
“…Perhaps activation of this pathway alone was not sufficient to afford long-term protection against apoptotic cell death. Notably, we did not detect an increase in either JAK-STAT or ERK 1/2, both of which have been shown to play important roles in G-CSF-related neuroprotection (Solaroglu et al, 2006).…”
Section: Discussioncontrasting
confidence: 70%
See 4 more Smart Citations
“…Perhaps activation of this pathway alone was not sufficient to afford long-term protection against apoptotic cell death. Notably, we did not detect an increase in either JAK-STAT or ERK 1/2, both of which have been shown to play important roles in G-CSF-related neuroprotection (Solaroglu et al, 2006).…”
Section: Discussioncontrasting
confidence: 70%
“…G-CSF has been shown to be beneficial in animal studies in a variety of brain injury models (Solaroglu et al, 2006), and is presently in Phase I/II trials for ischemic stroke in humans (Shyu et al, 2006, Schabitz et al, 2006. In the present study we found that treatment with G-CSF was associated with a transient improvement in T-maze spontaneous alternation and a trend towards improved body weight, but that it conferred no long-term benefit (Figure 1B,D).…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations